Attorney General John Van de Kamp Keynotes Fresno County Bar Association Law Day Luncheon - Watkins, Howard::::::::: (1983)
Howard Watkins presenting the Fresno County Voluntary Legal Services Program's Pro Bono Attorney of the Year Award to John McGregor; both shaking hands Fresno County Bar Association President-Elect Rodney Worrel, Stephen Kane